2000
DOI: 10.1021/bi992235x
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the D-Pathway in Reconstituted Site-Directed Mutants of CytochromecOxidase fromParacoccus denitrificans

Abstract: Heme-copper terminal oxidases use the free energy of oxygen reduction to establish a transmembrane proton gradient. While the molecular mechanism of coupling electron transfer to proton pumping is still under debate, recent structure determinations and mutagenesis studies have provided evidence for two pathways for protons within subunit I of this class of enzymes. Here, we probe the D-pathway by mutagenesis of the cytochrome c oxidase of the bacterium Paracoccus denitrificans; amino acid replacements were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
126
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(136 citation statements)
references
References 45 publications
10
126
0
Order By: Relevance
“…A similar mutation has also been reported at the equivalent position (N131D) in the oxidase from Paracoccus denitrificans (10). The N139D mutant of theR.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…A similar mutation has also been reported at the equivalent position (N131D) in the oxidase from Paracoccus denitrificans (10). The N139D mutant of theR.…”
supporting
confidence: 69%
“…The question being addressed in the current work is whether mutating N207 to aspartate has a similar effect on the enzyme as does the N139N mutation. It has been shown that the equivalent mutation in the oxidase from P. denitrificans (N199D) results in decoupling the proton pump (10), but no additional characterization of this mutant has been reported. It is confirmed in the current work that the N207D mutant oxidase from R. sphaeroides also does not pump protons, similar to the behavior of N139D.…”
mentioning
confidence: 99%
“…Mutagenesis experiments have been performed on the equivalent residues: D399 in the P. denitrificans aa 3 -type oxygen reductase, D407 in the R. sphaeroides aa 3 -type oxygen reductase, and D407 in the Escherichia coli bo 3 -type oxygen reductase (14,27,(43)(44)(45)(46). The D399N mutation in the P. denitrificans oxidase does not significantly change the properties of the oxidase, whereas the D399L mutant has only ∼7% activity and does not pump protons (41). These data are similar to those reported in the current work with the T. thermophilus enzyme.…”
Section: Previous Results From Mutating the Equivalent Of D372 In A-fmentioning
confidence: 99%
“…They appear to form a continuous network through hydrogen bonding between waters and with hydrophilic side chains, broken only by a conserved asparagine pair that forms a bridge interrupting the chain toward the entrance (13,(16)(17)(18). Several hydrophilic residues in the D pathway are crucial for the function of proton uptake, as evidenced by the effects of their mutation on enzyme activity and proton pumping efficiency (16,(19)(20)(21), in some cases inhibiting and others uncoupling activity.…”
Section: Resultsmentioning
confidence: 99%